The secular enlightenment - Jacob, Margaret C. (Princeton University Press, 2019)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- List of Images -- Acknowledgments -- Prologue -- 1 The Setting: Space Expanded and Filled Anew -- 2 Time Reinvented -- 3 Secular Lives -- 4 Paris and the Materialist Alternative: The Widow Stockdorff -- 5 The Scottish Enlightenment in Edinburgh -- 6 Berlin and Vienna -- 7 Naples and Milan -- 8 The 1790s -- Epilogue -- Glossary of Names -- Notes -- Index